Teaching middle level social studies : a practical guide for 4th-8th grade - Roberts, Scott L.; Wellenreiter, Benjamin R.; Ferreras-Stone, Jessica; Strachan, Stephanie L.; Palmer, Karrie L. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"This textbook is a comprehensive and practical guide to teaching middle level social studies. Middle level students are just as capable as high school students at engaging in hands-on, progressive, reflective activities, yet pedagogical strategies designed specifically for the middle grades are often overlooked in teacher education programs. This text provides both progressive and traditional teaching methods and strategies proven effective in the middle level classroom. The content of the book consists of conventional chapters found in most texts, such as "What is Social Studies?" and "Unit and Curriculum Planning," as well as unique chapters such as "The Middle Level Learner" and "Best Practices for Teaching State History." In addition to the unique chapters and lesson plans many additional features of the book will be useful for middle level teaching and learning. These features include: A list of website resources that provide links to thousands of lesson plans, state and national standards, and other multimedia tools that can be used in the classroom. Individual, collaborative, and whole class activities that will help methods students develop a better understanding of the topics, lessons, and strategies discussed. High quality lesson ideas and classroom tested teaching strategies embedded throughout the book. Images of student work samples that will methods students visualize the finished product that is being discussed. An examination of state and national standards that will help guide methods students in their lesson planning"--